A GENRE ANALYSIS OF RIA RICIS AND ATTA HALILINTAR'S PROMOTIONAL CAPTIONS ON INSTAGRAM - Putri Rizki Lestari, - (2019)
This study aims to discover the generic structure and lexico-grammatical features of Ria Ricis and Atta Halilintar's promotional captions on Instagram. There were some frameworks used to guide this research, such as Bhatia's levels of generic description (1997, 2005) Gerot and Wignell's explanations about the generic structure of descriptive, procedure, and recount text (1995), and Halliday's transitivity analysis (2014). The qualitative method was used to conduct this research. The results show that promotional captions could consist of descriptive, procedure, and recount texts with different generic structures and lexico-grammatical features for each text type. The generic structure of procedure text in promotional captions is pressure tactics-goal-steps, while the generic structure of recount text is orientation-events-pressure tactics. On the other hand, the generic structure of descriptive text is identification-product details-positive evaluations. Relational Processes dominate descriptive texts, while Material Processes appear frequently in procedure texts. In terms of recount texts, Ria Ricis' recount texts are dominated by Material Processes while Atta Halilintar's recount texts are dominated by Material Processes, Mental Processes, and Behavioral Processes.